2020
DOI: 10.3389/fonc.2020.558454
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Immune Checkpoint Inhibitors in Older Non-small-Cell Lung Cancer Patients: A Meta-Analysis

Abstract: Background: Immune checkpoint inhibitors (ICIs) have transformed the treatment landscape among non-small-cell lung cancer (NSCLC) patients. The efficacy of ICI therapy in older patients (≥65 years) is controversial and not fully clarified. We performed a systematic review and meta-analysis to evaluate the efficacy of ICIs in patients with advanced or metastatic NSCLC based on age (<65 years vs. ≥65 years). Methods: A comprehensive literature search for eligible randomized control phase II/III trials that compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(44 reference statements)
3
13
0
Order By: Relevance
“…Consistently, the HR for death among patients with stage IV NSCLC aged ≥75 years who received ICIs was smaller than that among those who did not receive ICIs (1.23 vs. 1.32). These results suggest that aging does not negatively impact ICI efficacy in patients with stage IV NSCLC, in line with these previous reports 8,12,14–17 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, the HR for death among patients with stage IV NSCLC aged ≥75 years who received ICIs was smaller than that among those who did not receive ICIs (1.23 vs. 1.32). These results suggest that aging does not negatively impact ICI efficacy in patients with stage IV NSCLC, in line with these previous reports 8,12,14–17 …”
Section: Discussionsupporting
confidence: 92%
“…An Italian multicenter retrospective study investigated the efficacy and safety of anti‐PD‐1 immunotherapy among patients with advanced NSCLC aged ≥75 years and found that the efficacy and toxicity of ICIs in elderly patients were comparable with the profiles observed in younger patients 14 . A meta‐analysis showed that ICI therapy and non‐ICI therapy of NSCLC had comparable efficacy in patients aged ≥65 years and those aged <65 years 15 . Another meta‐analysis of a large clinical dataset suggested that NSCLC patients aged ≥65 years can benefit even more from ICI therapy than younger patients 16 .…”
Section: Discussionmentioning
confidence: 99%
“…First, a higher tumor mutation burden (TMB) was used for prediction of better durable clinical benefit (DCB) of immune checkpoint inhibitors (ICIs) in younger patients [ 37 ]. The poorer response of older patients to ICIs may be related to immunosenescence characterized by decreased T cell proliferation, which is considered an age-related change in the immunity of the host, suggesting that patients with increased age had a worse response to ICI therapy that may influence the efficacy of ICIs in elderly people with a high prevalence of malignancies [ 38 ]. Finally, treatment-related AEs occur less often in younger patients than in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown that age is not an independent predictor of prognosis in cancer patients treated with ICIs. For example, Sun et al revealed that there was no significant difference in the OS of patients with NSCLC using PD-1/PD-L1 inhibitors between the young group (< 65 years old) and the old group (≥65 years old) (12). At the cutoff point of 70 years old, the PFS and OS of patients treated with ICIs in the melanoma, NSCLC and pan-cancer datasets were similar (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%